11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Frequencies and demographic determinants of breastfeeding and DHA supplementation in a nationwide sample of mothers in Germany - Libuda, Lars; Stimming, Madlen; Mesch, Christina; Warschburger, Petra; Kalhoff, Hermann; Koletzko, Berthold Viktor; Kersting, Mathilde (European Journal of Nutrition)

Lunch at school, at home or elsewhere. Where do adolescents usually get it and what do they eat? Results of the HELENA Study - Müller, Katrin; Libuda, Lars; Diethelm, Katharina; Huybrechts, Inge; Moreno, Luis A.; Manios, Yannis; Mistura, Lorenza; Dallongeville, Jean; Kafatos, Anthony; González-Gross, Marcela; Cuenca-García, Magdalena; Sjöström, Michael; et al. (Appetite)

Effects of lunch on children’s short-term cognitive functioning: a randomized crossover study - Müller, K; Libuda, Lars; Gawehn, N; Drossard, C; Bolzenius, K; Kunz, C; Kersting, M (European Journal of Clinical Nutrition)

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

„Do You Speak Usability?“ – Aktueller Stand des Glossars und des Curriculums für den „Certified Professional for Usability and User Experience (CPUX)“ der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter; Polkehn, Knut

Contextual tagging in the coactive knowledge organization - K {\ "u} hnel, Birger

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten

Computer science and education - A struggle for creative sovereignty in society? - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix (FIfF-Kommunikation)

Media contexts - context media - Keil, Reinhard

A Taxonomy-Based Approach Towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard

A Crook is a Crook … But is He Still a Crook Abroad? - On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

A crook is a crook ... but is he still a crook abroad? On the effect of immigration on destination-country corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

Musical Variants in Encoding, Analysis and Visualization - Kepper, Johannes; Roland, Perry; Röwenstrunk, Daniel (Balisage: The Markup Conference 2013)

Bildung für nachhaltige Entwicklung. Den Alltag gestalten – Teilhabe ermöglichen. Verbraucherbildung als Aufgabe von Schule - Oepping, Anke; Schlegel-Matthies, Kirsten (Schule NRW. Amtsblatt des Ministeriums für Schule und Weiterbildung)

Ethik, Konsumentenverantwortung und Verbraucherbildung im Spannungsfeld - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))

Fachliche Betreuung des Schwerpunktthemas: Ethik – Konsum – Verbraucherbildung. - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))

Ernährungs- und Verbraucherbildung im Unterricht - Oepping, Anke; Schlegel-Matthies, Kirsten

Business Model Representations: A Cross-Disciplinary Review of the Pragmatic, Semantic and Syntactic Foundations of Existing Approaches - John, Thomas; Kundisch, Dennis (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

A Review of the Effects of Lunch: On Adults’ Short-term Cognitive Functioning - Müller, Katrin; Libuda, Lars; Terschlüsen, Anna Maria; Kersting, Mathilde (Canadian Journal of Dietetic Practice and Research)
Because of widespread irregular lunch consumption by both children and adults, information on the effects of lunch on short-term cognitive functioning is relevant to public health. In September 2012, a MEDLINE search was conducted for studies in which the effects of lunch on cognitive performance were examined. Eleven experimental studies published from 1981 to 1996 were found and evaluated; all involved adults. In three studies, the effects of lunch and lunch skipping were compared; the remaining studies involved a determination of the effects of lunch size and lunch composition. Results of studies in which lunch was compared with no lunch indicate that lunch leads to potential impairment of some aspects of cognitive functioning in the early afternoon. Lunch size may influence cognitive functioning, with impairment more likely to occur after a large lunch than a small lunch. Furthermore, in comparison with low-fat lunches, high-fat lunches seem to result in slower but more accurate responses to some cognitive tasks. However, these suggestions must be viewed with caution, as they are based on only a few studies and are not thoroughly supported by high-quality evidence. In addition, results obtained with adults are not applicable to children. Thus, the potential effects of lunch need further examination in children and adults.